Lipid Profile and Menopausal Status - Al - Dahhan, Fouad Hamad; Al - Naama, Lamia M.; Disher, *Ahlam (AL-Kindy College Medical Journal, 2008)
Background: Dyslipidemia is a major cause ofcardiovascular disease, which in turn, is the mostcommon cause of female morbidity and mortality.Postmenopausal women (natural and surgical) are athigher risk of developing cardiovascular disease,especially coronary artery atherosclerosis.Objective: To observe the relationship between bloodlipids: total cholesterol (TC), high density lipoproteincholesterol (HDL-C), low density lipoproteincholesterol (LDL-C), triglycerides (TGs), and very lowdensity lipoprotein- cholesterol (VLDL-C), LDL-C/HDL-C ratio (atherogenic index) and menopausalstatus, and to determine the co-factors that may explainthis relationshipMethods: A prospective, cross-sectional study, whichincludes 279 women, age range from 35-55 yearsagreed to participate in this study. They were dividedinto 4 groups according to their menopausal status.These were pre-, peri post- natural and surgical postmenopausal. Data were collected from participants in apre-coded questionnaire and an overnight fasting bloodsample was collected for biochemical analysis.Results: Postmenopausal women had higher levels oflipids than pre or peri-menopausal. TC concentrationand LDL-cholesterol levels were higher in natural andsurgical menopause than in pre and pri-menopausalwomen (p